Impact of Biomass Burning on Ozone, Carbon Monoxide, and Nitrogen Dioxide in Northern Thailand - Khodmanee, Suratsawadee; Amnuaylojaroen, Teerachai (Frontiers in Environmental Science, 2021)
The problem of smoke haze pollution in Northern Thailand affects both the environment and residents. The main sources of smoke are wildfires and open burning during the dry season, which release many pollutants, especially surface O3, impacting health and causing an air pollution crisis. The aim of this research is to study the impact of biomass burning on the surface O3, CO and NO2 levels in Northern Thailand using the Weather Research and Forecasting Model with Chemistry (WRF-Chem). The simulation domain was configured with two domains with a grid spacing of 50 and 10 km in March 2014. To elucidate the effect of biomass burning, the model simulation was conducted for two cases—1) a simulation with anthropogenic, biogenic, and biomass burning emissions; 2) a simulation excluding biomass burning emissions. Owing to the model performance, the diurnal temperature and precipitation were consistent with observations, as indicated by Index of Agreement (IOA) ranges of 0.74 to 0.76, while those of O3, CO, and NO2 were in the range of 0.12 to 0.71. The results show that biomass burning increased O3, CO, and NO2 levels by 9%, 51%, and 96%, respectively.